Knowledge and practice of testicular self-examination among male students at Universiti Putra Malaysia - Mohd Sham, Zulfikar Irfan; Hamzah, Siti Aishah; Suchi, Umiaziente; Abas, Razif; Makhdzir, Norafisyah (Universiti Putra Malaysia Press, 2025)
Introduction: Testicular cancer poses a significant public health threat, especially among young men, underscoring the importance of testicular self-examination (TSE) as a vital preventive measure. Despite its significance, awareness and adherence to TSE guidelines remain low, particularly among university students. This study aims to assess the knowledge and practice of TSE among male students at Universiti Putra Malaysia (UPM) to bridge this gap in understanding. Methods: Conducted between January and April 2020 at UPM, this cross-sectional study targeted male students aged 18 to 30 from non-medical faculties, selected via random sampling. Data collection involved online surveys distributed to participants, with statistical analyses utilizing descriptive and inferential methods. Results: The study unveiled a concerning lack of TSE awareness and practice among male UPM students. A majority reported never having performed TSE, indicating a significant gap in preventive healthcare behaviours. Sociodemographic factors such as age, marital status, and level of education influenced TSE knowledge and practice, underscoring the necessity for tailored interventions to address these disparities. Conclusion: This study highlights the pressing need for targeted educational interventions to bolster TSE awareness and encourage regular practice among young men, especially university students. By overcoming barriers to TSE uptake and equipping individuals with the knowledge and skills to monitor their testicular health effectively, we can enhance health outcomes and alleviate the burden of testicular cancer in this demographic. Future research should explore the efficacy of diverse educational strategies and engage healthcare providers in promoting testicular health awareness.